PENERAPAN ETIKA KERJA ISLAMI UNTUK MENGEMBANGKAN PRODUKTIVITAS KERJA KARYAWAN DI PERUSAHAAN PUSAT GONI SURABAYA - Fina Tazkiyatul Mufidah; Johan Wahyu Wicaksono (Dinar : Jurnal Prodi Ekonomi Syariah, 2025)
This study aims to examine the implementation of Islamic work ethics among employees at Pusat Goni Surabaya. The selection of Pusat Goni Surabaya as the research site is based on the author's direct observations and involvement with the company, ensuring alignment with the characteristics of the issues examined. Additionally, the author's interest in the subject serves as a motivation to conduct an in-depth exploration of the company. From a practical perspective, the availability of data and supporting sources further justify the feasibility of this research. Strengthening Islamic work ethics among employees is also expected to enhance their work productivity. Given that employees play a crucial role in achieving organizational goals, it is essential for them to adhere to the established Islamic work ethics. This study is expected to provide valuable insights for the company regarding the implementation of Islamic work ethics. This research employs a descriptive method with a qualitative approach. The data sources consist of both primary and secondary data. Data collection methods include interviews, observations, and documentation. The collected data is analyzed through data reduction, data presentation, and conclusion drawing, which is verified through data triangulation to ensure accuracy. The findings indicate that the implementation of Islamic work ethics at Pusat Goni Surabaya has positively contributed to employee productivity and work quality. Despite certain challenges, continuous improvement efforts will support the company's long-term success. By upholding Islamic values, the company can serve as a model for the implementation of Islamic work ethics in the business sector. However, challenges remain, particularly in employees' educational backgrounds, which limit their understanding of product innovation. Additionally, the implementation of Islamic cultural practices, such as communal prayer before starting work, has yet to be fully optimized